Enhancing cereal productivity by genetic modification of root architecture. Issue 7 (18th May 2022) - Kořínková, Nikola; Fontana, Irene M.; Nguyen, Thu D.; Pouramini, Pouneh; Bergougnoux, Véronique; Hensel, Goetz
Abstract: Food security is one of the main topics of today's agriculture, primarily due to increasingly challenging environmental conditions. As most of humankind has a daily intake of cereal grains, current breeding programs focus on these crop plants. Customized endonucleases have been included in the breeders' toolbox after successfully demonstrating their use. Due to technological restrictions, the main focus of the new technology was on above‐ground plant organs. In contrast, the essential below ground components were given only limited attention. In the present review, the knowledge of the root system architecture in cereals and the role of phytohormones during their establishment is summarized, and the underlying molecular mechanisms are outlined. The review summarizes how the use of CRISPR‐based genome editing methodology can improve the root system architecture to enhance crop production genetically. Finally, future research directions involving this knowledge and technical advances are suggested. Graphical Abstract and Lay Summary: Food security is a crucial topic in today's agriculture. Previous studies have mainly focused on aboveground plant structures. This review summarises how CRISPR‐based genome editing technologies can improve the root system architecture to increase crop yield.